SOE Corporate Governance Reform in Lithuania - Explained & Еmpirically Tested - Jurkonis, Liudas; Merkliopas, Šarūnas; Gabulas, Deividas (Ekonomika, 2023)
Following previous research on management efficiency of state-owned enterprises (SOEs) in Lithuania, this paper continues previous discussion via extension of the observed time period seeking to continuously analyze the impact of corporate governance principles to the management effectiveness of Lithuanian SOEs. For the purpose of this study, elements of corporate governance principles established in the initial reform of the SOEs in Lithuania are used as key dependent variables to measure and quantify the dynamics of corporate governance culture and its impact to the management efficiency of SOEs. Analysis performed is of a special importance as it covers the 10-year period (2010–2020) and could serve as a case study in analyzing practical implications of managerialism principles in public sector and SOEs specifically. New public management paradigm (Politt, 1993) combined with policy learning theory (Bennett, Howlett, 1992) are used as the theoretical background to explain the initiation and logical framework of SOE reform as well as the selection of variables used in this study. Additionally, principles of corporate governance established by OECD and other international organizations (OECD, 2015) are also used to enrich the analytical framework. The results of the analysis do not only prove that the implementation of corporate governance principles has a positive influence on the efficiency of management of SOEs, but also reveals additional factors that were not identified in the previous research – this impact is not static, but rather dynamic changing in accordance with the maturity of managerial practices within SOEs. The revealed dynamic nature of effects of the SOE policy should lead to the continuation of research seeking to expand it both geographically and vertically including other governmental organizations into the scope of future research.